Analysis of the Influence of Psychological Capital and Work Motivation on Employee Performance in Financing Distribution with Employee Satisfaction as an Intervening Variable (Study at PT Permodalan Nasional Madani Venture Capital) - Wahyudin, Dian; Winarto, Oetami P. (International Journal Labs, 2025)
This study aims to analyze the effect of psychological capital and motivation on employee performance in financing distribution, with job satisfaction as an intervening variable. Psychological capital, which includes self-efficacy, optimism, hope, and resilience, plays an important role in improving employee motivation and performance. In addition, motivation is a key factor that encourages employees to work more effectively in achieving financing distribution targets. This study uses a quantitative approach with the Structural Equation Modeling (SEM) method to analyze the relationship between variables. Data was collected through a survey of employees involved in the financing distribution process at financial institutions. The findings show that psychological capital and motivation have a positive and significant impact on employee performance, both directly and indirectly through job satisfaction. Furthermore, job satisfaction is shown to act as a mediating variable that strengthens the relationship between psychological capital, motivation, and employee performance. These results suggest that companies need to pay attention to developing psychological capital and increasing employee motivation to improve job satisfaction, which in turn has a positive impact on their performance in disbursing financing. Therefore, organizations are encouraged to implement strategies that support psychological well-being and employee motivation to optimize work productivity.